2019
DOI: 10.3390/pharmaceutics11120667
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Squalene Oil-Based Emulsion Adjuvants Employing a Self-Emulsifying Drug Delivery System and Assessment of Mycoplasma hyopneumoniae-Specific Antibody Titers in BALB/c Mice

Abstract: In this study, a self-emulsifying drug delivery system (SEDDS) was employed to prepare novel squalene oil-based emulsion adjuvants. Deionized water, 0.01% and 0.02% (w/v) carbomer solutions of C-971P NF and C-940 grades were used to prepare emulsions containing 3%, 5% and 10% of squalene oil. Altogether 15 candidate emulsions were prepared and used as adjuvants for the delivery of a combination vaccine containing a porcine circovirus type 2 (PCV2) antigen and inactivated Mycoplasma hyopneumoniae (J101 strain) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 52–54 SNEDDS technology is a lipid-based drug delivery system that has attracted the attention of the pharmaceutical industry and is considered to be a promising drug carrier for improving the oral bioavailability of poorly soluble drugs. 55 To date, many commercial SNEDDS drugs have been approved by FDA, such as kaletra ® (Ritonavir/Lopinavir), Aptivus ® (Tipranavir), Sandimmune ® (cyclosporine). 17 , 56 Given the advantages of the SNEDDS technology and its application in medicine, this study used it to increase the solubility and enhance the bioavailability of GKA.…”
Section: Discussionmentioning
confidence: 99%
“… 52–54 SNEDDS technology is a lipid-based drug delivery system that has attracted the attention of the pharmaceutical industry and is considered to be a promising drug carrier for improving the oral bioavailability of poorly soluble drugs. 55 To date, many commercial SNEDDS drugs have been approved by FDA, such as kaletra ® (Ritonavir/Lopinavir), Aptivus ® (Tipranavir), Sandimmune ® (cyclosporine). 17 , 56 Given the advantages of the SNEDDS technology and its application in medicine, this study used it to increase the solubility and enhance the bioavailability of GKA.…”
Section: Discussionmentioning
confidence: 99%
“…The measured droplet size shows that the emulsion contained droplets (358.57–811.60 nm) of similar or slightly smaller size compared to other squalene-based oil-in-water emulsions 41 ( Table 2 ). In general, the droplet size of emulsion used in the pharmaceutical products ranges from 0.1 to 10 µm, 15 , 42 suggesting that prepared emulsions (F1–F15) were of suitable sizes for use as an adjuvant.…”
Section: Discussionmentioning
confidence: 75%
“…A previous study reported the use of two types of non-ionic surfactants, Span ® 80 and Cremophor ® ELP, for 3%, 5%, and 10% of squalene-based oil-in-water emulsions as adjuvants for the delivery of a combination vaccine containing a porcine circovirus type 2 (PCV2) antigen and inactivated Mycoplasma hyopneumoniae (J101 strain) antigen. 41 As a result, a particle size of up to 2.5 µm was obtained, and the zeta potential exhibited values ranging from -43 mV to +11 mV. 41 Our emulsions (Span ® 85, Kolliphor ® RH40, and CMC) showed droplet sizes in the nano range and maintained zeta potential values between −30 mV to -10 mV for 4 weeks, indicating good physical stability as a vaccine adjuvant.…”
mentioning
confidence: 98%
See 1 more Smart Citation